Developing Contextual-Based Learning Materials For Local Guides - Pasek, Made; Ratminingsih, Ni Made; Seken, I Ketut (Jurnal Pendidikan Indonesia, 2017)
This research aimed at developing contextual-based learning materials for local guidesat Ambengan village. It was research and development using modified Borg and Gall’s R&D model. There were eight steps conducted in order to develop the learning materials namely, need analysis, writing course grid, first draft, expert judgment, revision I, field test, revision II, and final product. From the data analysis, it was found that (i) the local guides required English learning materials which canimprove their speaking skill and help them to conduct waterfall trekking tour;(ii) The development of the materials should consider some criteria of good learning materials and follow task based model as a framework of the developed English learning materials; (iii) the developed English learning materials were categorized as excellent; and (iv) thematerials were effective in improving learners ‘speaking skill since there was an improvement from the post-test I, post-test II, post-test III.